2021
DOI: 10.1002/jor.25211
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related cellular and microstructural changes in the rotator cuff enthesis

Abstract: Rotator cuff injuries increase with age. The enthesis is the most frequent site of rotator cuff injury and degeneration. Understanding age‐related changes of the enthesis are essential to determine the mechanism of rotator cuff injuries, degeneration, and to guide mechanistically driven therapies. In this study, we explored age‐related cellular changes of the rotator cuff enthesis in young, mature, and aged rats. Here we found that the aged enthesis is typified by an increased mineralized zone and decreased no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Smaller dog breeds are known to have a higher life expectancy than large dog breeds, which explains the higher number of smaller dogs with higher ages and in contrast, reduced prevalence of HPRLL in this age group. In a rat‐model study, an increased mineralized zone and decreased non‐mineralized zone of the enthesis was found in aging rotator‐cuff entheses 25 . Although comparable studies in dogs are lacking, age‐related increased mineralization of the entheses could have increased the radiographic visibility of the enthesis in older dogs in our study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Smaller dog breeds are known to have a higher life expectancy than large dog breeds, which explains the higher number of smaller dogs with higher ages and in contrast, reduced prevalence of HPRLL in this age group. In a rat‐model study, an increased mineralized zone and decreased non‐mineralized zone of the enthesis was found in aging rotator‐cuff entheses 25 . Although comparable studies in dogs are lacking, age‐related increased mineralization of the entheses could have increased the radiographic visibility of the enthesis in older dogs in our study.…”
Section: Discussionmentioning
confidence: 46%
“…In a rat-model study, an increased mineralized zone and decreased non-mineralized zone of the enthesis was found in aging rotator-cuff entheses. 25 Although comparable studies in dogs are lacking, age-related increased mineralization of the entheses could have increased the radiographic visibility of the enthesis in older dogs in our study. Other degenerative changes of the enthesis, accompanied by calcifying metaplasia, is another potential explanation for the radiographic visibility of the enthesis.…”
Section: Cadaver Specimen Analysesmentioning
confidence: 68%
“…It was also reported that thickness and area of both uncalcified fibrocartilage and calcified fibrocartilage were changed based on age. 27…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that that thickness and area of both uncalcified fibrocartilage and calcified fibrocartilage change based on age. 27 Nevertheless, we carefully selected knees without osteoarthritis or ACL deficiency to reduce age-related discrepancies. Second, the ligament attachment angle depends on the knee flexion angle.…”
Section: Discussionmentioning
confidence: 99%
“…While the above discussion has focused on repair of articular cartilage, some of the principles discussed can also be applied to the healing of other connective tissues of the MSK system, including menisci, intravertebral discs (IVD), as well as ligaments and tendons. In the case of tendons, tendons in different locations exhibit different properties [ 185 ], tendon properties can change with aging [ 74 , 186 , 187 ] and some tendons, such as the supraspinatus, can undergo age-related degeneration without overt symptoms [ 188 , 189 , 190 ]. Thus, cell therapy treatment could be envisioned to address tendinopathies rather than overt ruptures.…”
Section: The Way Forwardmentioning
confidence: 99%